Odpowiedź :
Odpowiedź:
zadanie 5
[tex](3 - 4 {a}^{2} + 5a) + ( - 3a + 5 {a}^{2} + 3) = 3 - 4 {a}^{2} + 5a - 3a + 5 {a}^{2} + 3 = 6 + {a}^{2} + 2a[/tex]
[tex]9a + 5 + (2b + 3a - b) - 10b = 9a + 5 + 2b + 3a - b - 10b = 12a + 5 - 9b[/tex]
[tex](4 {a}^{2} {b}^{2} + 7x {b}^{2} ) - (3ab + 13a {b}^{2} ) - (5 {a}^{2} {b}^{2} + 5ab) + {a}^{2} {b}^{2} = 4 {a}^{2} {b}^{2} + 7x {b}^{2} - 3ab - 13a {b}^{2} - 5 {a}^{2} {b }^{2} - 5ab + {a}^{2} {b}^{2} = 7x {b}^{2} - 8ab - 13a {b}^{2} [/tex]
zadanie 6
[tex]2( {x}^{2} + 3y - 12) = 2 {x}^{2} + 6y - 24[/tex]
[tex]8( - 12x + y) + 12x = - 96x + 8y + 12x = - 84x + 8y[/tex]
[tex] - 3(2 {x}^{2} -3 xy) + 2(3 {x}^{2} - 3xy - x) = - 6 {x}^{2} + 9xy + 6 {x}^{2} - 6xy - 2x = 3xy - 2x[/tex]
zadanie 7
[tex](3a + 4)(a - 5) = 3 {a}^{2} - 15a + 4a - 20 = 3 {a}^{2} - 11a - 20[/tex]
[tex]( - a + b)(5a - b) = - 5 {a}^{2} + ab + 5ab - {b}^{2} = - 5 {a}^{2} + 6ab - {b}^{2} [/tex]
[tex](4 - 5a)(3 {a}^{2} - a - 2) = 12 {a}^{2} - 4a - 8 - 15 {a}^{3} + 5 {a}^{2} + 10a = 17 {a}^{2} + 6a - 8 - 15 {a}^{3} [/tex]